PENGARUH PEMBIAYAAN IJARAH DAN MURABAHAH TERHADAP PROFITABILITAS PADA BANK BRI SYARIAH DI OTORITAS JASA KEUANGAN (OJK) - Baso Akib; Riska Riska (Jurnal Akuntansi dan Keuangan Syariah (Jurnal Akunsyah), 2022)
This study aims to (1) describe the effect of Ijarah financing on profitability at BRI Syariah Banks registered with the Financial Services Authority (OJK), (2) to describe the effect of Murabahah financing on profitability at BRI Syariah Banks registered with the Financial Services Authority (OJK), (3) To describe Ijarah and Murabahah financing on profitability at BRI Syariah Banks registered with the Financial Services Authority (OJK).Type of research in this research is descriptive quantitative. The data used is secondary data with data collection techniques using observation and documentation. Multiple linear regression analysis method. The population in this study is all financial reports at BRI Syariah Banks registered with the Financial Services Authority (OJK) for the 2016-2020 period, the sample used in this study was 60 samples, the data analysis technique used IBM SPSS 21. The results show that partially (1) partially Ijarah financing has a significant effect on profitability at BRI Syariah Banks registered with the Financial Services Authority (OJK) (2) partially Murabahah financing has a significant effect on profitability at BRI Syariah Banks registered with the Financial Services Authority. Finance (OJK (3) Simultaneously Ijarah and Murabahah financing have a significant effect on profitability at BRI Syariah Banks registered with the Financial Services Authority (OJK). The implications of research results regarding Ijarah and Murabahah financing variables which are suspected to have a significant relationship with profitability (ROA) simultaneously or together and have a major influence on the profitability (ROA) of BRI Syariah Bank..